Peranan Edukasi Ilmu Parenting dalam Mencegah Dampak Negatif Media Sosial Terhadap Pembentukan Karakter Anak di Kota Makassar - Mahrany, Yunita; Alwi, Alimin; Najamuddin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
In the digital era, social media has a great influence on children's character development. Uncontrolled use of social media can lead to negative impacts, such as device addiction, lack of social skills, and vulnerability to content that is not in accordance with moral values. Therefore, parenting education becomes a crucial aspect in helping parents guide children in utilising social media wisely and responsibly. This study aims to analyse the role of parenting education in preventing the negative impact of social media on children's character building in Makassar City. Using a qualitative method with a descriptive approach, data were collected through interviews and literature studies. The research subjects involved parents and educators who have experience in parenting in the digital era. The results showed that good parenting education can help parents instil positive values such as discipline, empathy, responsibility, and emotional intelligence in children. In addition, parenting education also increases children's awareness of social norms and equips them with skills in sorting out information and managing the use of social media wisely. Collaboration between the government, educational institutions, and the community in providing quality parenting education is an important step in shaping the character of children who are smart, ethical, and ready to face the challenges of the digital world.